х - 56 * 2 = 850
х - 112 = 850
х = 850 + 112
х = 962
962 - 56 * 2 = 850
962 - 112 = 850
850 = 850
748 + 205 + х = 2 000
953 + х = 2 000
х = 2 000 - 953
х = 1 047
748 + 205 + 1 047 = 2 000
953 + 1 047 = 2 000
2 000 = 2 000
х + 89 * 3 = 748
х + 267 = 748
х = 748 - 267
х = 481
481 + 89 * 3 = 748
481 + 267 = 748
748 = 748
2 * х + 1 457 = 10 267
2 * х = 10 267 - 1 457
2 * х = 8 810
х = 8 810 : 2
х = 4 405
2 * 4 405 + 1 457 = 10 267
8 810 + 1 457 = 10 267
10 267 = 10 267
Так как b + c = 7 5/11 (дм), то: a = P - (b+c) = 8 - 7 5/11 = 6/11 (дм)
И, соответственно, b = P - (a+c) = 8 - (6/11 + 2 6/7) = 8 - 262/77 =
= 8 - 3 31/77 = 4 46/77 (дм)
Проверим: Р = a+b+c = 6/11 + 2 6/7 + 4 46/77 =
= 42/77 + 220/77 + 354/77 = 616/77 = 8 (дм)
ответ: 6/11 дм; 2 6/7 дм; 4 46/77 дм.